Проблемы внедрения инновационных образовательных технологий в региональном вузе - Успанова, Ж.К. (My University, 2016)
The article considers the problems of formation of innovative infrastructure in the regional university.High school now occupies the most important place in the model provides a systematic introduction of the achievements of science and technology in the real economy.0t is necessary to create conditions for the integration of innovative educational technologies in the national industrial and economic syste
Keywords: regionaluniversity; high education; innovation; innovative technologies; personnel training